The impact of business performance on dividend policy of companies listed on Vietnam stock market - Nguyen, Thi Thao Linh (H. : ĐHQGHN, 2020)
The study focuses on the factors in the business performance that affect the dividend policy of listed companies on the Vietnamese stock market in 2007. In general, the firms have a dividend payout ratio at level of low and the difference of that ratio that is ot too large among enterprises.